ASUPAN ZAT GIZI, STATUS GIZI DAN STATUS KESEHATAN PADA BALITA YANG MENDAPATKAN PMT-P - Aghnita, Kiki Angreancy (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Children who experience malnutrition disorder will experience less physicalgrowth and mental disorders. Restore additional feeding program is one of the efforts intackling the problem of poor nutrition and lack of nutrition. This study aims to evaluatethe intake of nutrients, nutritional status and health status in toddlers who get PMTRecoveryin the working area in Bengkulu City Clinics 2016. This research is descriptiveresearch with cross sectional approach. Sampling purposive sampling technique was donewith as many as 43 samples. Data were collected through a questionnaire that has beenfilled by the mother of a toddler through the interview process which was then in theanalysis are univariate and bivariat. The results showed that intake of nutrients (energy,protein, fat and carbohydrates) toddler respondents have earned PMT-P average includescategories less than a number of nutritional adequacy. Toddler health status ofrespondents have earned PMT-P was almost entirely never experienced pain during thelast month. Based on the results of the statistical tests are known that there is ameaningful difference between the nutritional status before and after nutrition status on atoddler who has been getting PMT-P in the city of Bengkulu. P-PMT program that hasbeen running should be more optimized so that nutritional problems in toddlers can behandled. The need for monitoring back on intake of nutrients, nutritional status and healthstatus of toddlers who have been getting PMT-P in an attempt to increase the success ofthe program.